Potency of Mahakam Delta in East Kalimantan, Indonesia - Zairin Zain; Sahala Hutabarat; Slamet Budi Prayitno; Ambaryanto Ambaryanto (International Journal of Science and Engineering, 2014)
Mahakam Delta is not only utilized for fishery activities but also for several industrial purposes such as coal and oil mining, shipping and timber. The objective of this paper is to provide information in term of the potency of Mahakam Delta located in East Kalimantan province, Indonesia. The study was conducted in Mahakam Delta, East Kalimantan Province, Indonesia. Participatory rural appraisal is a group of methods to collect information in a participatory fashion from rural communities. The method employed in this research was descriptive analysis describing the environmental potency found in Mahakam Delta. Massive conversion of mangrove forest particularly Nypa (Nypa fruticans) area into pond has driven conflict among related stakeholders on the utilization of natural resource and land which subsequently impacts on the fish and shrimp source regeneration, loss of ecological functions of mangrove forest for feeding, nursery and spawning ground of fish and other organisms. Besides of fisheries, oil and gas activity also exists in Mahakam Delta. Mahakam Delta is regarded as important area due to the largest producer of oil and gas mining. Thus, oil and gas industry is the most reliable sector that contributes to the economic development of Kutai Kartanegara district. As a resource provider, Mahakam Delta ecosystem provides various resources for livelihoods. As a life-support service provider, Mahakam Delta ecosystem provides habitat and ideal environment to support variety of living kinds. As a convenience provider, Mahakam Delta ecosystem provides unique and interesting recreation site. As a protector from natural disaster, Mahakam Delta ecosystem is able to protect human kinds from natural disaster threatening coastal area.